Overview of Automatic Testing Methods of Fuzzing Based on Machine Learning Techniques - Tomasz TURBA and Krzysztof ZATWARNICKI (Communications of International Proceedings, 2022)
Automated testing methods play an essential role in enhancing software security and development. Recent papers researching fuzzing are concentrating on applications that leverage machine learning approaches to overcome its primitive limitations. This article examines current research on the use of machine learning to automated fuzzing. It specifically examines fuzzer types, machine learning technological potential, and briefly discusses issues found in own research conducted. Future research to alleviate fuzzing bottlenecks is defined in this paper as authors thoughts.
Keywords: Fuzzing; Machine Learning; Deep Learning; Testing.